Case report: Primary intracranial EWs/PNET in adults: Clinical experience and literature review - Hu, Xianwen; Huang, Qi; Wang, Ju; Li, Dandan; Wang, Pan; Cai, Jiong (Frontiers in Oncology, 2022)
Introduction: Adult primary intracranial Ewing sarcomas (EWs)/primitive neuroectodermal tumors (PNET) are extremely rare, with only 30 patients published before us. The imaging features and treatment strategies of primary intracranial EWS/PNET are unclear due to its rarity. The aim of this study was to investigate the clinical features, imaging findings, treatment, survival analysis and prognosis of adult EWS/PNETs, and a systematic review was conducted based on the patient we treated and published literature. Case Description: A 19-year-old male patient suffered head pain due to an accidental fall on a motorcycle more than 10 days ago, and underwent computed tomography (CT) examination and found that the left temporo-occipital fossa was occupied. Magnetic resonance imaging (MRI) was recommended to understand the nature of the lesion and the result showed that it is a high probability of meningioma. He underwent surgical removal of the mass under general anesthesia, and surprisingly, postoperative pathology revealed EWs/PNET. The disease has a high degree of malignancy, and the patient developed multiple metastases throughout the body 5 years after surgery. Conclusion: Primary intracranial EWs/PNET in adult patients are rare, of which imaging findings should be considered as one of the differential diagnoses of meningioma, hemangiopericytoma, and malignant triton tumor. Larger solid-cystic masses with septum-like enhancement may be relatively specific imaging findings of intracranial EWs/PNETs. The prognosis of primary adult intracranial EWs/PNETs is poor. Radical tumor resection combined with radiotherapy and chemotherapy are currently the main and possibly the most effective treatment methods.